2015
DOI: 10.1186/s12889-015-2261-9
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering risky behaviors of expatriate teenagers in the United Arab Emirates: A survey of tobacco use, nutrition and physical activity habits

Abstract: BackgroundTobacco use and unhealthy lifestyle habits amongst youth contribute to most major health issues in the United Arab Emirates (UAE) and worldwide. However up to date and comprehensive statistics are not available on the current behavior, experimentation and environmental influences on teenagers in the UAE’s expatriate community, who are greatly impacted by the country’s culture and environment, as well as bringing influences from their cultures of origin. Expatriates comprise a majority of the UAE popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 14 publications
5
26
1
1
Order By: Relevance
“…As (4). In another study using the same cohort studied here, we identified not only a gap in health education but also an inefficacy of anti-tobacco laws and campaigns (5). In light of these findings, health education has unexplored potential.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…As (4). In another study using the same cohort studied here, we identified not only a gap in health education but also an inefficacy of anti-tobacco laws and campaigns (5). In light of these findings, health education has unexplored potential.…”
Section: Introductionmentioning
confidence: 51%
“…Zachary D. Stanley 1* , Leena W. Asfour 2* , Michael Weitzman 3,5,6 and Scott E. Sherman 4,5 Mise en oeuvre d'un modèle d'éducation en santé axé sur l'intervention des pairs aux Émirats arabes unis : lutter contre les comportements à risque des adolescents expatriés RÉSUMÉ La consommation de tabac parmi les jeunes est en augmentation aux Émirats arabes unis, et le pays se classe au quinzième rang mondial pour la prévalence du diabète de type 2. Les expatriés constituent une majorité de la population, ce qui fait d'eux un sous-ensemble important à étudier.…”
Section: Implementation Of a Peer-mediated Health Education Model In unclassified
See 1 more Smart Citation
“…*Current PA guidelines for children were defined as physically active on all 7 days for a total of at least 60 minutes per day during the past week; **Current AAP sedentary behavior or screen-time guidelines were defined as limiting total media time (including new media such as cell phones, tablets, and social media) to no more than 2 h/d; 24 ***Current PA guidelines for adults were defined as adults attaining a minimum of 30 minutes of moderate-intensity aerobic (endurance) physical activity on 5 days each week or 20 minutes of vigorous-intensity aerobic physical activity for a minimum on 3 days each week. 25 6 a nationally representative household survey that included PA data on male and female Emirati children (aged 6 to 10 years; N = 253) and adolescents (aged 11 to 18 years; N = 276); a school-based study 14 conducted in 2010 using a representative sample of UAE national and expatriate adolescents (aged 12 to 18 years; N = 1018) from the city of Al Ain (Abu Dhabi emirate); and a school-based study 21 conducted in 2014 using a convenient sample of expatriate children (N = 439 9th grade highschool) were used to inform the grade for Overall Physical Activity Levels. Based on these findings a split grade of D-/F-was awarded with the minus sign indicating disparities between subgroups and a reduction in PA over time.…”
Section: Organized Sportmentioning
confidence: 99%
“…In 2004, a study on 1475 private secondary school students in the emirate of Dubai showed that 41.2% of school children 'regularly' (defined in the study as sport practiced at least 3 times a week throughout every month of the year) participated in sport and 13.2% reported participation in sports clubs based outside of schools. 23 A school-based study 21 conducted in 2014 using a convenient sample of expatriate children (N = 439 9th grade high-school) from 5 private high schools in Abu Dhabi city reported that 66.0% of the sample participated in at least 1 or more sports teams during the past 12 months. The RWC decided that there was a lack of robust and nationally representative data for all 7 emirates related to organized sport participation.…”
Section: Organized Sport Participation: Incmentioning
confidence: 99%